Relación entre la cultura tributaria y la evasión tributaria en el mercado productores de la ciudad Iquitos periodo 2024 - Tuesta Torres, Aldana Muriel (2025)
This study analyzes the relationship between tax culture and tax evasion in the farmers' market of the city of Iquitos during the period 2024. Using a quantitative approach and a non-experimental cross-sectional design, questionnaires are applied to 140 vendors to measure variables. key factors such as trust in tax institutions, knowledge of tax obligations and the perception of risk of sanctions. The results revealed a significant negative evaluation between tax culture and tax evasion, suggesting that a higher level of tax culture is associated with a lower tendency to evade taxes. Furthermore, a strong positive pressure was found between trust in tax institutions and the perception of risk of sanctions, which indicates that taxpayers who trust in SUNAT perceive a greater risk of being sanctioned. Contrary to expectations, knowledge of tax obligations showed a negative relationship with the intention to evade taxes, underscoring the importance of tax education. The research conclusions highlight the need to strengthen tax culture, improve institutional transparency and promote tax education programs to reduce evasion in this context.